A BLENDED LEARNING IN ICT USED FOR IMPROVING ENGLISH LANGUAGE TEACHING - Gumartifa, Asti; Larasati, Finza; Aurelia, Syafira (PROJECT (Professional Journal of English Education), 2020)
The technology of information and communication (ICT) has evolved in the sector of education. Many elements have dramatically changed exponentially over the past three decades. It can modify and simplify the development of learning activities. Thus, Google Classroom will provide a blended learning platform in the education aspect. Google Classroom provides various things simpler for teachers to conduct learning practices effectively and efficiently, not the expected learning just in class, but even outside the classroom. It is revolutionizing schooling, thus the combination of mixed-method learning is also needed by each school. The advent of blended is among the most significant outcomes of the revolution. Learning which incorporates the essence of face-to-face and ICT use is needed in the era of 4.0. This article discusses existing theories, and empirical evidence relating to the essence of blended learning and Google Classroom in ELT. This research is used to create teachers’ broad mind widely to the use of Google Classroom as the blended course in English Language Teaching.